PERAN JABATAN FUNGSIONAL AUDITOR TERHADAP PENINGKATAN KINERJA BIROKRAT DI LINGKUNGAN INSPEKTORAT PROVINSI JAWA TENGAH - Pardosi, Debora Angelia (Kopertis Wilayah X, 2018)
The spirit of reform encourages the State Civil Apparatus to carry out renewal and improvement of the system in the development, improvement and service of the community in order to encourage the community and support the implementation of good governance in public administration. Supervision carried out by. The Government, has determined the Functional Position of Auditors who have the scope, duties, responsibilities, and authority to carry out internal supervision on government agencies, institutions or other parties in it. For this reason, this research has two problems. First, how is the role of JFA in improving the performance of bureaucrats in the Central Java Province Inspectorate. Second. What obstacles were encountered by JFA in the supervision process of the performance of Bureaucrats in the Central Java Province Inspectorate. This problem was examined using a sociological juridical approach. In the sociological juridical approach, law as law in action is described as an empirical social phenomenon. The results of this study confirm that: First, there are 2 (two) roles of JFA in improving the performance of bureaucrats in the Central Java Province Inspectorate, namely: Improving the system of internal supervision and control, and improving the quality and professionalism of resources. Secondly, there were several factors encountered by JFA in the supervision process of the performance of bureaucrats in the Central Java Province Inspectorate that had to be immediately corrected to support good governance in public administration.